2022
DOI: 10.3390/ijms231810216
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miR-29 Family in TGF-β Driven Fibrosis in Glaucomatous Optic Neuropathy

Abstract: Primary open angle glaucoma (POAG), a chronic optic neuropathy, remains the leading cause of irreversible blindness worldwide. It is driven in part by the pro-fibrotic cytokine transforming growth factor beta (TGF-β) and leads to extracellular matrix remodelling at the lamina cribrosa of the optic nerve head. Despite an array of medical and surgical treatments targeting the only known modifiable risk factor, raised intraocular pressure, many patients still progress and develop significant visual field loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 133 publications
3
16
0
Order By: Relevance
“…When incorporating only protein-coding isoforms and removing the truncated isoforms from the analysis, the gene expression fold-change increased from 9 to 62-folds (Pcorr=3.15x10 -183 ). This overexpression of canonical COL1A1 in the TME can be explained by the absence of miR-29 silencing, as previously described 50 . The miR-29 family is known to be an EMT inhibitor 50 .…”
Section: Long-read Sequencing Captures Germline and Somatic Mutations...supporting
confidence: 77%
See 2 more Smart Citations
“…When incorporating only protein-coding isoforms and removing the truncated isoforms from the analysis, the gene expression fold-change increased from 9 to 62-folds (Pcorr=3.15x10 -183 ). This overexpression of canonical COL1A1 in the TME can be explained by the absence of miR-29 silencing, as previously described 50 . The miR-29 family is known to be an EMT inhibitor 50 .…”
Section: Long-read Sequencing Captures Germline and Somatic Mutations...supporting
confidence: 77%
“…This overexpression of canonical COL1A1 in the TME can be explained by the absence of miR-29 silencing, as previously described 50 . The miR-29 family is known to be an EMT inhibitor 50 . Its silencing through the TGFβ pathway correlates with the upregulation of ECM-encoding genes, including multiple collagens, as reported in the present study.…”
Section: Long-read Sequencing Captures Germline and Somatic Mutations...supporting
confidence: 77%
See 1 more Smart Citation
“…MiR-29 is a family of miRNAs which are strongly anti-fibrotic in their effects on the TGF-β signaling pathway and the regulation of extracellular matrix production and deposition. In their review, Smyth et al [ 6 ] discuss the anti-fibrotic effects of miR-29 and the role of miR-29 in ocular pathology and in the development of glaucomatous optic neuropathy. A better understanding of the role of miR-29 in POAG may aid in developing diagnostic and therapeutic strategies for patients with this common optic neuropathy.…”
Section: Reviewsmentioning
confidence: 99%
“…Consistent with previous studies, our findings also demonstrated that miR-29c targets collagen gene expression in the retina. The expression of the miR-29 family was reported to significantly decrease in the ECs of patients suffering from Fuchs endothelial corneal dystrophy (FECD) [183]. Thus, overexpression of miR-29b and miR-29c resulted in a considerable downregulation of several ECM genes such as COL1A1, COL4A1, and LAMC1 in corneal EC.…”
Section: Non-coding Rnas and Amdmentioning
confidence: 99%